429 Long-term analysis of MASTERKEY-265 phase 1b trial of talimogene laherparepvec (T-VEC) plus pembrolizumab in patients with unresectable stage IIIB-IVM1c melanoma. (9th November 2020) - Long, Georgina; Dummer, Reinhard; Johnson, Douglas; Michielin, Olivier; Martin-Algarra, Salvador; Treichel, Sheryl; Chan, Edward; Diede, Scott; Ribas, Antoni
Abstract : Background: Previous findings from the MASTERKEY-265 phase 1b study showed that the combination of T-VEC and pembrolizumab was well tolerated and produced a high complete response (CR) rate of 43% in patients with advanced melanoma. 1 The 3-year progression-free survival (PFS) and overall survival (OS) rates at that time were 53.6% and 71%, respectively. Here, we report the results of the long-term follow-up efficacy analyses. Methods: The MASTERKEY-265 phase 1b trial (NCT02263508 ) was an open-label, single-arm study that enrolled patients who had unresectable, stage IIIB-IVM1c melanoma with injectable, measurable lesions and no prior systemic treatment. T-VEC was administered intralesionally at the approved dosing starting day 1 of week 1. Pembrolizumab (200 mg) was administered intravenously Q2W beginning on day 1 of week 6. The maximum treatment period was 2 years. The primary endpoint was dose-limiting toxicities; key secondary endpoints included objective response rate and PFS per modified irRC, OS, and safety. Results: As of the data cutoff (Mar 2, 2020), all 21 patients enrolled were off treatment; 6 died and 15 are in long-term follow-up. The median follow-up time was 58.6 months (range: 1.4–61.6). The CR rate remained 43% (9/21 patients). Twelve of the 13 responders (92.3%) are still in response, including all 9 patients with a CR. Median duration of response was not reached (range: 2.8+–54.3+ months). Median PFS and OS were not reached at the data cutoff. KM estimates of 4-year PFS and OS rates were 55.9% and 71.4%, respectively, which have held stable since the 3-year analysis. Patients who achieved a CR or partial response had better OS (p=0.0056) compared to those who did not respond. Median OS for non-responders was 24.4 months and was not reached for responders. No additional safety signals were detected. Conclusions: At almost 5 years of follow-up, median PFS and OS were not reached for patients treated with the combination of T-VEC and pembrolizumab in this phase 1b study of unresectable metastatic melanoma. 92% of responders remained in response with improved OS observed in responders compared with non-responders. The corresponding randomized phase 3 trial has completed enrollment and is currently ongoing. Trial Registration: NCT02263508 Ethics Approval: The study was approved by the Ethics Board of each institution involved in this study and can be produced upon request. Reference: Long G, Dummer R, Andtbacka R, et al. Follow-up analysis of MASTERKEY-265 Phase 1b (ph1b) trial of talimogene laherparepvec (T-VEC) in combination (combo) with pembrolizumab (pembro) in patients (pts) with unresectable stage IIIB–IVM1c melanoma (MEL). Pigment Cell Melanoma Res 2019;32:133–134.